From the Appellative of Wierzba to the Anthroponym of Wierzbiński - Marciniak-Firadza, Renata (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The purpose of the article is to highlight connections of the common name of wierzba [Eng. “willow”] and the proper name Wierzbiński. The author discusses the etymology of the word wierzba and its meaning in the history of the Polish language, both in contemporary Polish and in its dialects. Next, the author explains the word and phraseological relationships with the wierzba appellative as well as with derived words, which are both common and proper names. The source material for the analysis was excerpted from dictionaries of the Polish language: etymological, general (explanatory: historical and contemporary dictionaries), dialectal, phraseological, and onomastic.